ANTIMICROBIAL TREATMENT BEFORE DENTAL PROCEDURES IN PATIENTS WITH BACTERIAL ENDOCARDITIS - Adriana Krasteva; Assya Krasteva; Angelina Kisselova-Yaneva (Peytchinski Publishing, 2010)
Infective endocarditis is a rare condition with significant morbidity and mortality. It may arise following bacteraemia in a patient with a predisposing cardiac lesion. In an attempt to prevent this disease, over the past 50 years, at-risk patients have been given antibiotic prophylaxis before dental procedures.